Pengaruh Kepercayaan Diri dan Pilihan Kata/Diksi terhadap Ketrampilan Berbicara Siswa di Sekolah Menengah Pertama Negeri Kepulauan Seribu Jakarta - mardiana, mardiana (Jurnal Pendidikan Manajemen Transportasi, 2022)
ABSTRACT Mardiana. The Effects of Self-Confidence and Choice of Diction towards Students’ Speaking Skill at State Junior High Schools in Kepulauan Seribu Jakarta Speaking with a good choice of diction will be greatly affect a person's level of confidence, making it easier to communicate smoothly. This research is aimed to get emperical data by analyzing the effects of self-confidence and choice of diction towards students’ speaking skill at state junior high schools in Kepulauan Seribu Jakarta. Samples are taken 86 respondents from students at grade 8 at state junior high schools at SMPN 133 Pulau Pramuka, at SMPN 241 Pulau Tidung and at SMPN 260 Pulau Untung Jawa in Kepulauan Seribu Jakarta. The research sample obtained through simple random sampling method that researchers mix the subjects in the population so that all subjects are considered equal. Data collective done by giving a dialogue to students to test speaking skill, a questionaire given to measure of self confidence whether it is high or low (30 items), and a test for choice of diction (multiplechoice/25 items). Collected data were analyzed using a descriptive statistical analysis and test data requirements (test for normality and linearity test), correlation and linear regression. The results of the research are concluded: 1) There are any significant effects of self confidence and choice of diction jointly towards students' speaking skills. That is proved by the value of Fo = 17,884 and Sig. 0,000 < 0,05; 2) There is a significant effect of self confidence towards the students' speaking skills. That is proved by the value of to = 2,654 and Sig. 0,010 < 0,05; 3) There is a significant effect of choice of diction towards students' speaking skills. That is proved by the value of t0 = 3,734 and Sig. 0,000 < 0,05. This may imply that students’ speaking skill is affected by self-confidence and choice of diction.